Influência da estrutura ambiental na composição da assembleia de aves urbanas, em um bairro residencial de Bauru-SP - Itaya, Isabela [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
Anthropogenic actions are responsible for environmental homogenization and species extinction. Urban areas are extremely distinct from undisturbed areas, presenting challenges for wildlife. Because birds are great bioindicators of environmental quality, they have been increasingly studied to understand the impact of urbanization on the bird assemblage. Factors of the urban environment, such as impermeabilization of the surface, the extent of vegetation cover, the presence of artificial structures, interaction with exotic fauna and with humans and environmental pollution, directly affect urban avian assemblages. The objective of this study was to define the assemblage of urban birds in a residential area, in the city of Bauru-SP, and to verify the influence of the environmental structure in the composition of urban avifauna. Ten point-count throughout the sample area were used and the samples occurred monthly, in two different periods (morning and afternoon), for a year (October/2020 to September/2021). The urban bird assemblage and bird diversity parameters were correlated with the environmental structure, both biotic (e.g. number of trees, shrubs, palms, etc.) and abiotic (e.g. number of posts, buildings, etc), verifying if there is a correlation between the composition of the avifauna and the environmental structure, defining which factors influence the most in the spatial distribution of birds species. 83 species were recorded, with a predominance of Tyrannidae and Thraupidae families and invertebrate predators, granivorous, omnivorous and mixed-stratum foraging species. In addition, the correlation between some species of birds and functional groups with structures of the urban environment were analyzed.

As áreas urbanas são extremamente distintas de ambientes inalterados, apresentando inúmeros desafios para a vida silvestre. As aves, por serem ótimos bioindicadores de qualidade ambiental, vem sendo cada vez mais estudadas para entender o impacto da urbanização na assembleia de aves. Fatores do ambiente urbano, como a impermeabilização da superfície, a extensão de cobertura vegetal, a presença de estruturas artificiais, a interação com fauna exótica e com os seres humanos e a poluição ambiental, afetam diretamente a avifauna urbana. Este trabalho tem como objetivo caracterizar a assembleia de aves urbanas em um bairro residencial, no município de Bauru-SP e analisar a influência da estrutura do ambiente na estruturação da avifauna urbana. Foram utilizados 10 pontos de contagem espalhados pela área amostral e as amostragens foram realizadas uma vez por mês em dois períodos distintos, de manhã e de tarde, durante um ano (outubro/2020 a setembro/2021). A composição específica e os parâmetros de diversidade de aves foram correlacionados com a estrutura do ambiente, tanto biótica (e.g. número de árvores, arbustos, palmeiras, etc.) quanto abiótica (e.g. número de postes, número de edifícios, etc.), verificando se há correlação entre a composição da avifauna e a estrutura ambiental, definindo quais fatores mais influenciam na distribuição espacial das espécies de aves. Foi registrada uma riqueza de 83 espécies, com predominância de da famílias Tyrannidae e Thraupidae, e de espécies predadoras de invertebrados, granívoras, onívoras e que forrageiam em estrato misto. Além disso, foi analisada a correlação entre algumas espécies de aves e de grupos funcionais com determinadas estruturas do ambiente urbano.
Influence of the environmental structure on the composition of the urban bird assemblage, in a residential neighborhood of Bauru-SP
Keywords: Birds; Urbanization; Aves; Urbanização; Bauru (SP)